3D ski boot deformation from distributed IMUs - Dallain, S.; Desbiens, A. L. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Ski boots are an important piece of equipment for alpine skiing: they play a vital role both in protecting the skier from injuries and transmitting loads to the ski. Ski boots exhibit complex nonlinear material deformation under load [1]. Measuring those deformations in-run could provide valuable information for manufacturers (e.g. optimizing mass) and for users (e.g. choosing an appropriately stiff boot). Various methods have already been tested: angular potentiometers [2], electrogoniometers [2] and strain gauges [3]. A new method is proposed which uses distributed IMUs. This could provide a less intrusive, more accurate, complete 3D deformation of ski boot at multiple locations even through the presence of mechanical joints, large shell deformations and liner compression.